Roosting behaviour and habitat selection of Pteropus giganteus reveal potential links to Nipah virus epidemiology. Issue 2 (3rd February 2014) - Hahn, Micah B.; Epstein, Jonathan H.; Gurley, Emily S.; Islam, Mohammad S.; Luby, Stephen P.; Daszak, Peter; Patz, Jonathan A.; McKenzie, Ailsa
Summary Flying foxes Pteropus spp. play a key role in forest regeneration as seed dispersers and are also the reservoir of many viruses, including Nipah virus in Bangladesh. Little is known about their habitat requirements, particularly in South Asia. Identifying Pteropus habitat preferences could assist in understanding the risk of zoonotic disease transmission broadly and, in Bangladesh, could help explain the spatial distribution of human Nipah virus cases. We analysed characteristics of Pteropus giganteus roosts and constructed an ecological niche model to identify suitable habitat in Bangladesh. We also assessed the distribution of suitable habitat in relation to the location of human Nipah virus cases. Compared to non‐roost trees, P. giganteus roost trees are taller with larger diameters and are more frequently canopy trees. Colony size was larger in densely forested regions and smaller in flood‐affected areas. Roosts were located in areas with lower annual precipitation and higher human population density than non‐roost sites. We predicted that 2–17% of Bangladesh's land area is suitable roosting habitat. Nipah virus outbreak villages were 2·6 times more likely to be located in areas predicted as highly suitable habitat for P. giganteus compared to non‐outbreak villages. Synthesis and applications. Habitat suitability modelling may help identify previously undocumented Nipah outbreak locations and improve our understanding of Nipah virus ecology by highlighting regions where there is suitable bat habitat but no reported human Nipah virus. Conservation and public health education is a key component of P. giganteus management in Bangladesh due to the general misunderstanding and fear of bats that are a reservoir of Nipah virus. Affiliation between Old World fruit bats (Pteropodidae) and people is common throughout their range, and in order to conserve these keystone bat species and prevent emergence of zoonotic viruses, it is imperative that we continue to improve our understanding of Pteropus resource requirements and routes of virus transmission from bats to people. Results presented here can be utilized to develop land management strategies and conservation policies that simultaneously protect fruit bats and public health.